Measles or not measles? that is the question! (2021)
We present a diagnostically challenging case of a patient who presented with fever and rash during a measles outbreak. The diagnosis was complicated by the interpretation of the results of serological tests, which resulted in implementation of major preventive measures in the hospital. The patient was later confirmed to have murine typhus.